Strategi Komunikasi Pustaka Lebah dalam Meningkatakan Brand Awareness - Jessica; Agustrijanto (UNIVERSITAS KALBIS, 2022)
Pustaka Lebah is one of the children's book publishers who already have a good reputation since 2002. In 2014 Pustaka Lebah experienced obstacles in selling products produced, due to competition with several other children's magazine publishers, one of which was children's magazine BOBO. Besides this there are several other factors that hinder the sale of products in the Pustaka Lebah, namely the lack of quality human resources and the content that is created does not match the target audience on the Pustaka Lebah social media on Instagram. The purpose of this research is to find out how to increase brand awareness of Pustaka Lebah through Instagram in increasing sales with the method used is descriptive qualitative. The final result of this study is so that readers can find out how to increasing brand awareness of Pustaka Lebah through Instagram in increasing sales